A Comparative Study of Treatment of Chronic Backache Between Conventional Method and Trigger Point Injections (TPI) (Journal of Armed Forces Medical College, Bangladesh, 2009)
Non-specific low backache of mechanical origin is common symptoms of disability in the community. There are many causes of low backache; these are mechanical and non-mechanical types. The commonest form of low backache is structural dysfunction that has direct relationship with activity. There are many regimens of treatment of low backache and trigger points injection (TPI) is one modality of them. This comparative study between TPI and conventional treatment of chronic backache was carried out at Combined Military Hospital (CMH) Bogra over a period of one year where 60 patients were treated. Out of 60 patients, 30 patients in group-I was given conventional treatment and other 30 patients in group-II were provided TPI. The mean age distribution was 42.33±5.79 years in group-I and 43.76±6.35 years in group-II, mean weight of the patients was 73.43±7.2 kg in group-I and 74.46±8.04 kg in group-II. Mean height of the patients were 165.33±9.84 cm in group-I and 166.50±9.10 cm in group-II. Mean duration of backache was 33.86 ±16.89 months in group-I and 32.10.±14.53 months in group- II and male female ratio was 18:12 in group-I and 22: 8 in group-II. In group-II TPI was provided, where their mean sessions of TPI requirement was 4.1±1.21. After treatment, their mean visual analogue scale (VAS) was 4.77±0.76 in group-I and 3.81±0.84 in group-II which is not statistically significant and duration of mean pain relief was 3.78±0.79 months in group-I and 5.65±1.21 months in group-II which is statistically significant. TPI is not a new modality of treatment of pain but it is not commonly practice in this country; which can be adopted for pain management usually without side effect. Key Words: Backache, Trigger point injection (TPI).   doi: 10.3329/jafmc.v5i1.2850 JAFMC Bangladesh. Vol 5, No 1 (June) 2009 pp.37-40